The impact of alcohol misuse on fathering in Northern Uganda: An ethnographic study of fathers. (February 2021) - Mehus, Christopher J.; Wieling, Elizabeth; Thomas Oloya, Okot; Laura, Achan; Ertl, Verena
The Acholi people of northern Uganda experienced decades of conflict. Alcohol misuse is high among northern Ugandan men. This is common in displaced or post-war communities. Because parents are often the most significant and proximal influence in a child's development, it is important to understand the relationships between parental behavioral health and parenting. The purpose of this ethnographic study was to understand the impact of alcohol misuse on fathering, from fathers' perspectives. We collected qualitative data from several sources, including in-depth interviews with 19 fathers. Informants identified three ways in which a father can "overdrink": drinking to drunkenness, spending too much money on alcohol, or spending too much time drinking alcohol. Fathers described the specific ways in which overdrinking impacted each of the three primary roles of a father, which were identified as providing, educating, and creating a stable home. Of the negative effects of overdrinking, a compromised ability to provide for basic needs was described as the most salient. The findings suggest that support for families in this region should include support for father's substance misuse, as a father's overdrinking is widely understood to be problematic for the entire family.